Performance Of Lemna Sp. And Spirodela Sp. On Nutrient Removal From Fish Farm Wastewater - Neoh, Sun Hao (Universiti Sains Malaysia, 2017)
Phytoremediation employs plants to remove contaminated soil and wastewater. The effluents from aquaculture has large amount of suspended solids and enriched with nitrogen and phosphorus in aquatic ecosystems. By using conventional wastewater treatment to treat fishpond wastewater, the cost is expensive to run and maintain. The performance of phytoremediation by using macrophytes, such as Lemna sp. and Spirodela sp., are evaluated on treatment of fishpond wastewater. The duckweeds were fed with wastewater from Catfish production facility. The objective was to determine the nutrient update and its effect towards biomass. 4 pond rigs were set up to study. They were Spirodela sp., Lemna sp., mix (Lemna sp. and Spirodela sp.) and control (without plant). The water quality was monitored as well. The treatment by phytoremediation was done in raceway pond rig for 2 weeks. The efficiency of phosphate removal was 89% and 85% by Lemna sp. and Spirodela sp. respectively. Spirodela sp. reduced nitrate concentration to 3.6 mg/L, while Lemna sp. managed to reduce to 7.9 mg/l. Spirodela sp. archived 89.0% in phosphate removal efficiency compared to that of Lemna sp. at only 85.1%. Lemna sp. and Spirodela sp. reduced turbidity from 16.2 ± 4.0 NTU to 3.2 ± 2.4 NTU in just 6 days. However, both Lemna sp. and Spirodela sp. did not change much in pH value. COD volatile solids of fishpond wastewater. In overall, Lemna sp. and Spirodela sp. were good for nutrient removal, improve water quality and growth of biomass.